Nanotechnology for boosting ovarian cancer immunotherapy - Prabhjot Kaur; Santosh Kumar Singh; Manoj K. Mishra; Shailesh Singh; Rajesh Singh (BMC, 2024)
Abstract Ovarian cancer, often referred to as the "silent killer," is notoriously difficult to detect in its early stages, leading to a poor prognosis for many patients. Diagnosis is often delayed until the cancer has advanced, primarily due to its ambiguous and frequently occurring clinical symptoms. Ovarian cancer leads to more deaths than any other cancer of the female reproductive system. The main reasons for the high mortality rates include delayed diagnosis and resistance to treatment. As a result, there is an urgent need for improved diagnostic and treatment options for ovarian cancer. The standard treatments typically involve debulking surgery along with platinum-based chemotherapies. Among patients with advanced-stage cancer who initially respond to current therapies, 50-75% experience a recurrence. Recently, immunotherapy-based approaches to enhance the body's immune response to combat tumor growth have shown promise. Immune checkpoint inhibitors have shown promising results in treating other types of tumors. However, in ovarian cancer, only a few of these inhibitors have been effective because the tumor's environment suppresses the immune system and creates barriers for treatment. This hampers the effectiveness of existing immunotherapies. Nonetheless, advanced immunotherapy techniques and delivery systems based on nanotechnology hold promise for overcoming these challenges.